Exploring the Stock Price Correspondence to Oil Price Shocks In the Gulf Cooperation Council Countries: Evidence from Linear (Symmetric) Model - Alrub, Ahmad Abu; Rjoub, Husam; Aga, Mehmet; Bein, Murad (International Journal of Economics and Financial Issues, 2018)
This study investigates the linkage between oil price index and stock price index in six GCC countries in two folds. Firstly, it studies the long-run relationship linking the stock price Index (SPI) and the oil price Index (OPI) for the time span, beginning February 2002 to May 2015. After confirming the dependency of the SPI across cross-sectional units for the six GCC countries three types of panel cointegration tests were used. Pedroni; Kao which is an Engle-Granger two step residual based test, and Fisher which is a combined Johansen test. Secondly, it investigates the linear short-run effect of oil price index shocks on these markets by using bootstrapped resample residuals. The findings reveal a robust long-run relationship amid OPI and SPI of six GCC country members. Furthermore, the linear short-run results indicate significant and positive consequence on Oman, Qatar, and UAE of oil price index shocks. The findings also indicate that Qatar is the most oriented market for the oil price changes within a short time period. Keywords: Stock price, oil price, panel cointegration, bootstrapped resample residuals and linear short-run model. JEL Classifications: C65, C33, G14.